High Resolution DNA Typing of Human Leukocyte Antigen A29 in Familial Birdshot Chorioretinopathy. (17th February 2021) - Tsui, Edmund; Takhar, Jaskirat S.; Joye, Ashlin; Ahmad, Tessnim R.; Acharya, Nisha R.; Gonzales, John A.
ABSTRACT: Purpose : To describe high-resolution DNA typing of HLA-A29 in patients with familial birdshot chorioretinopathy (BSCR). Methods : A retrospective clinical chart review was performed of all patients at the Francis I. Proctor Foundation with BSCR with a documented family history of HLA-A29 positive BSCR. High-resolution HLA-A29 typing was performed for these patients. Results : Two families with familial BSCR were identified. Family 1 consisted of a mother, daughter and maternal aunt with BSCR. All were positive for the HLA-A29*02 allele. Family 2 consisted of two sisters with BSCR who were both positive for the HLA-A29*02 allele. Conclusions : Familial BSCR is rare and we report the high-resolution DNA typing of HLA-A29 in two families with familial BSCR and their associated clinical outcomes, including the first documented case of multigenerational BSCR.